Pengaruh Inflasi Terhadap Kurs Rupiah : Pendekatan Vektor Error Correction Model (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2020)
LUKMAN ADITYA, 2020 Influence of Inflation on the Rupiah Exchange Rate Vector Error Correction Model Approach, under the guidance of Michael as supervisor I and Muhammad Awaluddin as supervisor II.The purpose of this study was to determine the effect of Inflation on the Rupiah Exchange Rate Approach Vector Error Correction Model. This research is a quantitative study, using secondary data with a Vector Error Correction Model analysis tool using the Eviews application program Version 10.2.          The research results show that inflation in the short run has a positive effect on the rupiah exchange rate, inflation in the long run has a negative effect on the rupiah exchange rate.